Novel soluble thieno[3,2-b]thiophene fused porphyrazine - Casey,A; Han,Y; Wyatt,MF; Anthopoulos,TD; Heeney,M (RSC Advances, 2015)
The synthesis of the first soluble thieno[3,2-b]thiophene based porphyrazine (ZnTTPz) is reported from the cyclisation of 2,3-dicyano-5-octylthieno[3,2-b]thiophene. ZnTTPz can be considered the all thiophene analogue of naphthalocyanine. ZnTTPz exhibits a red-shifted absorption in solution and thin film, as well as a reduced band gap in comparison to the thiophene analogue due to an increased conjugation length. Films of ZnTTPz processed from solution exhibit p-type semiconducting behaviour in field-effect transistors with low hysteresis and reasonable charge carrier mobility.